SIMNET Concepts: Computer-Based Learning and Assessment for Computer Concepts (Using information technology: a practical introduction to computer and communications) - Brian K. William (mC Graw Hill, 2003)
File dalam bentuk Javascript, Media player, Gambar, Htm (Internet), dll; Isi: Data (Menus, Practice, Questionpool, dan StuDier), ie5setup (Flat, Ins, Messgr, dll), Setup-help, Simnet concepts, Window media player, dll; Judul Dalam Kemasan.